Exogenous surfactant replacement: how to deliver it? - Biban, P.; Chini, L.; Bonetti, et al., P. (Acta Biomedica Atenei Parmensis, 2012)
Exogenous surfactant is a therapeutic option for newborns, children and adults with acute respiratory distress disorders. Although tracheal instillation is still reputed as the classical method of surfactant delivery, alternative techniques have been investigated. Surfactant administration by using thin intra-tracheal catheters, bronchoscopy, laryngeal mask airway, or nebulisation, although variably effective, appear to be less invasive when compared to tracheal intubation. However, further research is still needed to better clarify this matter.